2012
DOI: 10.1177/0022034512460551
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary Analysis Suggests That AMTN is Enamel-specific and a Candidate for AI

Abstract: Molecular evolutionary analysis is an efficient method to predict and/or validate amino acid substitutions that could lead to a genetic disease and to highlight residues and motifs that could play an important role in the protein structure and/or function. We have applied such analysis to amelotin (AMTN), a recently identified enamel protein in the rat, mouse, and humans. An in silico search for AMTN provided 42 new mammalian sequences that were added to the 3 published sequences with which we performed the an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
57
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(61 citation statements)
references
References 27 publications
4
57
0
Order By: Relevance
“…No significant differences were detected in enamel thickness, enamel volume, or in rod decussation. These results are consistent with EST data showing only trace expression of Amtn and Klk4 in non-dental tissues, the decay of these genes in vertebrates that no longer make enamel [21,15,22], and the onsets of Amtn and Klk4 expression in transition ameloblasts [1620], following the secretory stage when enamel thickness, volume, and rod architecture are established. Taken together, these results strongly support the conclusion that AMTN and KLK4 are not essential for biological processes outside of the dentition or during the secretory stage of amelogenesis.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…No significant differences were detected in enamel thickness, enamel volume, or in rod decussation. These results are consistent with EST data showing only trace expression of Amtn and Klk4 in non-dental tissues, the decay of these genes in vertebrates that no longer make enamel [21,15,22], and the onsets of Amtn and Klk4 expression in transition ameloblasts [1620], following the secretory stage when enamel thickness, volume, and rod architecture are established. Taken together, these results strongly support the conclusion that AMTN and KLK4 are not essential for biological processes outside of the dentition or during the secretory stage of amelogenesis.…”
Section: Discussionsupporting
confidence: 90%
“…The human expressed sequence tag (EST) database (which does not include developing teeth) lists only 2 AMTN and 10 KLK4 ESTs out of a total of 3,328,811 ESTs for normal tissues. Amtn and Klk4 both appear to be functionally specific for dental enamel formation and are pseudogenized in species that have lost the ability to make teeth or dental enamel during evolution [21,15,22]. The Klk4 −/− mouse display severe maturation stage enamel malformations in the absence of systemic abnormalities [23,24] and defects in KLK4 cause an autosomal recessive, non-syndromic form of amelogenesis imperfecta (AI) [2527].…”
Section: Introductionmentioning
confidence: 99%
“…Of the hundreds of genes associated with tooth development, most are pleiotropic and perform essential functions outside of tooth development (15). By contrast, the aforementioned six genes have been hypothesized to be tooth-specific based on mutagenesis studies in mice, inactivation of these genes in one or more edentulous/enamelless vertebrate species, and natural genetic variation in humans that causes nonsyndromic amelogenesis imperfecta, dentinogenesis imperfecta, and dentin dysplasia (11)(12)(13)(16)(17)(18)(19)(20) (table S1). At the same time, other evidence indicates that these six genes are pleiotropic and are expressed outside of tooth development (21)(22)(23) (table S1).…”
Section: Parallel Tooth and Enamel Lossmentioning
confidence: 99%
“…Recently, our group successfully used this approach for predicting sensitive positions in various proteins of the secretory calcium-binding phosphoprotein family (26), and showed that missense mutations lead to genetic diseases. This approach was demonstrated on the following proteins: amelogenin (27), enamelin (28), matrix extracellular phospho-glycoprotein (29), amelotin (30), dentin matrix protein 1 (31), and ameloblastin. 6 Here, we perform the evolutionary molecular analysis of mammalian TNSALP to (i) highlight the functional or structural importance of various positions and domains; (ii) predict sensitive positions that should be responsible for a genetic disorder when substituted; and (iii) validate our predictions by using missense mutations reported in humans.…”
mentioning
confidence: 99%